-43=-61+x

Simple and best practice solution for -43=-61+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -43=-61+x equation:


Simplifying
-43 = -61 + x

Solving
-43 = -61 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-43 + -1x = -61 + x + -1x

Combine like terms: x + -1x = 0
-43 + -1x = -61 + 0
-43 + -1x = -61

Add '43' to each side of the equation.
-43 + 43 + -1x = -61 + 43

Combine like terms: -43 + 43 = 0
0 + -1x = -61 + 43
-1x = -61 + 43

Combine like terms: -61 + 43 = -18
-1x = -18

Divide each side by '-1'.
x = 18

Simplifying
x = 18

See similar equations:

| 4ay/3d | | (x+y)=80 | | 2x^2-8x-100=20 | | X/27/2 | | x^3-8x^2-33x+26=0 | | 5z-6+6=-36+z | | 9a+2a-8a-3b= | | 29b-93=7 | | 5(2x-10)/2 | | 3x+7=9x+5 | | 4v^2+25v+21=0 | | 16a+8b+1=0 | | 12-b=0 | | (-7b-2c)+(6b-3c-1)= | | X+3x+(x+7)=32 | | 8a(-3a)= | | 50=1.75x | | -((-3)+3)= | | 5x+8=9x-8 | | 16a+8a+1=0 | | b(b-3)=28 | | 0=-16x^2+1400 | | 12=780x | | 6x-46=4x+76 | | 19+1=20 | | 1600=-4x | | 6x+2+3x=74 | | x^4+5x^3+7x^2-4=0 | | -5(6b-8)=30-9b | | f(x)=-2x^3-4x^2-1 | | 7y/10-18=7/17/40 | | -8n-7n=29 |

Equations solver categories